1977
DOI: 10.1136/bmj.2.6087.603
|View full text |Cite
|
Sign up to set email alerts
|

Staging breast cancer: role of bone scanning.

Abstract: BRITISH MEDICAL JOURNAL 3 SEPTEMBER 1977 603 metoprolol, however, a dissociation between its lipolytic and cardiac actions was noted. These results indicate therefore differences in the metabolic effects of metoprolol, acebutolol, and propranolol but give no insight into the mechanisms concerned.Attempts to reduce blood lipid levels in patients with hyperlipaemia with beta-adrenoceptor antagonists have yielded inconsistent results."3'3 Carruthers and Taggart'5 have shown, however, that oxprenolol suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…It can be seen that the percentage of abnormal (single and multiple lesions) scans in the common malignancies such as carcinoma of the breast, lung or prostate is above 50% and therefore bone scanning is an important element in the management of these malignant diseases. In carcinoma of the breast, there are wide differences in the reported incidences of positive bone scan (1,2,4,7,8,14,18). Tofe et al (18) reported that in 28% of positive bone scans the primary was carcinoma of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that the percentage of abnormal (single and multiple lesions) scans in the common malignancies such as carcinoma of the breast, lung or prostate is above 50% and therefore bone scanning is an important element in the management of these malignant diseases. In carcinoma of the breast, there are wide differences in the reported incidences of positive bone scan (1,2,4,7,8,14,18). Tofe et al (18) reported that in 28% of positive bone scans the primary was carcinoma of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies designed to diagnose potentially treatable BOM at presentation have provided the positive yield of initial BI in BCa patients with more than three involved nodes. The reported frequencies of BOM have been between 9% and 16% [the larger percentage reflecting the small number of evaluated cases] (4,7).…”
Section: Clinical Summary Of Patients With Bone Metastases [Bom]mentioning
confidence: 99%
“…The histological examination of the skeletal system delivers important information despite the development of sensitive non-invasive imaging procedures. Results from earlier studies are controversial because dierent techniques were used to extract marrow and because selection criteria varied (Davies et al 1977;Diel et al 1992b;Shinozaki et al 1992;Landys and Stenram 1975). In contrast, bone biopsy is almost established in other ®elds such as hematology, endocrinology and osteology (Beckstead 1986;Burkhardt et al 1985;Landys 1982;Manegold et al 1986).…”
Section: Introductionmentioning
confidence: 99%